Integrated Analysis of Metatranscriptome and Amplicon Sequencing to Reveal Distinctive Rhizospheric Microorganisms of Salt-Tolerant Rice - Wenna Meng; Zhenling Zhou; Mingpu Tan; Anqi Liu; Shuai Liu; Jiaxue Wang; Zhiguang Sun; Yiluo Tan; Yan Liu; Baoxiang Wang; Yanming Deng (Plants)
Salt stress poses a significant constraint on rice production, so further exploration is imperative to elucidate the intricate molecular mechanisms governing salt tolerance in rice. By manipulating the rhizosphere microbial communities or targeting specific microbial functions, it is possible to enhance salt tolerance in crops, improving crop yields and food security in saline environments. In this study, we conducted rice rhizospheric microbial amplicon sequencing and metatranscriptome analysis, revealing substantial microbiomic differences between the salt-tolerant rice cultivar TLJIAN and the salt-sensitive HUAJING. Fungal taxa including Hormiactis, Emericellopsis, Ceriosporopsis, Dirkmeia, and Moesziomyces predominated in the rhizosphere of salt-tolerant rice, while bacterial genera such as Desulfoprunum and Hydrogenophaga exhibited notable differences. Metatranscriptomic analysis identified 7192 differentially expressed genes (DEGs) in the two rice varieties, with 3934 genes being upregulated and 3258 genes being downregulated. Enrichment analyses in KEGG and GO pathways highlighted the majority of DEGs were associated with the “two-component system”, “sulfur metabolism”, and “microbial metabolism in diverse environments”. The interaction network of DEGs and microbial taxa revealed upregulation of transporters, transcriptional factors, and chaperones, such as ABC transporters and chaperonin GroEL, in the rhizosphere microbiomes of salt-tolerant varieties. Our multi-omics network analysis unveiled that fungi like Ceriosporopsis and Dirkmeria, along with bacteria such as Desulfoprunum, Rippkaea, and Bellilinea, showed a positive correlation with flavonoid synthesis in salt-tolerant rice. This study provides an in-depth exploration of the distinctive microbial communities associated with the rhizosphere of salt-tolerant rice varieties, shedding light on the complex interactions between these microbial consortia and their host plants under stress conditions.